Pengaruh Kinerja Keuangan Perusahaan Terhadap Nilai Perusahaan dengan Good Corporate Governance Sebagai Variabel Moderating pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - B2041162011, Jum'an (Equator Journal of Management and Entrepreneurship (EJME), 2019)
THE INFLUENCE OF THE COMPANY'S FINANCIAL PERFORMANCE ON CORPORATE VALUE WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE IN MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGEJum’an1Program Studi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Tanjungpura  Dosen Pembimbing 1Mustaruddin, S.E., M.Si, Ph.DFakultas Ekonomi dan Bisnis Universitas Tanjungpura Dosen Pembimbing 2Dr. Wendy, S.E., M.Sc.Fakultas Ekonomi dan Bisnis Universitas Tanjungpura ABSTRACT This study wants to prove the influence of each variable which are Return On Equity (ROE), Debt to Equity Ratio (DER), and Current Ratio (CR) to the value of the company which is moderated by Good Corporate Governance in manufacturers listed on the Indonesian Stock Exchange (IDX). Based on previous research and associated with supporting theories proposed by experts using the EViews 9 program as a statistical data processing tool. This type of research is quantitative research. In this study, the researcher used purposive sampling technique. Research samples were 36 manufacturing companies from 2012-2016, with data analysis techniques using Moderated Regression Analysis (MRA).Based on data processing using MRA, it is proven that Return On Equity (ROE), Debt to Equity Ratio (DER), and Current Ratio (CR) has a positive and insignificant effect on company value. Moderation of The Audit Committee is unable to weaken or strengthen the relationship between Return On Equity (ROE) and company value. Moderation of  The Audit Committee is able to strengthen the relationship between the Debt to Equity Ratio (DER) and the Current Ratio (CR) to the value of the company. While the moderation of Independent Commissioners is not able to weaken or strengthen the relationship between Return On Equity (ROE), Debt to Equity Ratio (DER) and Current Ratio (CR) to company value.Keywords : Return On Equity (ROE), Debt to Equity Ratio (DER), Current Ratio (CR), Good Corporate Governance of company value, Audit Committee, Independent Commissioners.